2021
DOI: 10.1098/rstb.2020.0251
|View full text |Cite
|
Sign up to set email alerts
|

The role of vocal learning in call acquisition of wild grey seal pups

Abstract: Pinnipeds have been identified as one of the best available models for the study of vocal learning. Experimental evidence for their learning skills is demonstrated with advanced copying skills, particularly in formant structure when copying human speech sounds and melodies. By contrast, almost no data are available on how learning skills are used in their own communication systems. We investigated the impact of playing modified seal sounds in a breeding colony of grey seals ( Halichoerus grypus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The cultural transmission of vocalizations we hypothesize in the semi-solitary harbor seal is quite rare in non-social mammals but may occur in a few social ones, such as the naked-mole rat (Heterocephalus glaber) (Barker et al, 2021), grey seal (Halichoerus grypus) (Stansbury & Janik, 2021), and some cetaceans (for a review, see Garland & McGregor, 2020). This rarity may stem from a lack of evidence rather than negative evidence because vocal learning in mammals is much less studied than in birds.…”
Section: Converg Ing E Viden Ce From B Irds and Pinnipedsmentioning
confidence: 95%
“…The cultural transmission of vocalizations we hypothesize in the semi-solitary harbor seal is quite rare in non-social mammals but may occur in a few social ones, such as the naked-mole rat (Heterocephalus glaber) (Barker et al, 2021), grey seal (Halichoerus grypus) (Stansbury & Janik, 2021), and some cetaceans (for a review, see Garland & McGregor, 2020). This rarity may stem from a lack of evidence rather than negative evidence because vocal learning in mammals is much less studied than in birds.…”
Section: Converg Ing E Viden Ce From B Irds and Pinnipedsmentioning
confidence: 95%
“…The cultural transmission of vocalizations we hypothesize in the semi‐solitary harbor seal is quite rare in non‐social mammals but may occur in a few social ones, such as the naked‐mole rat ( Heterocephalus glaber ) (Barker et al, 2021), grey seal ( Halichoerus grypus ) (Stansbury & Janik, 2021), and some cetaceans (for a review, see Garland & McGregor, 2020). This rarity may stem from a lack of evidence rather than negative evidence because vocal learning in mammals is much less studied than in birds.…”
Section: Converging Evidence From Birds and Pinnipedsmentioning
confidence: 99%
“…The closely related grey seals may show similar vocal learning strategies: in a recent experiment, wild pups copied playback stimuli, becoming more accurate in imitations over time (Stansbury & Janik, 2021). Their fundamental frequency (f 0 ) matching became especially pronounced around 2–3 weeks of age, which may denote a sensitive period and cultural transmission of vocalizations in this phocid species (Stansbury & Janik, 2021). Further support comes from the case of Hoover, a human‐raised harbor seal pup (Ralls et al, 1985).…”
Section: Converging Evidence From Birds and Pinnipedsmentioning
confidence: 99%
“…A subsequent study on wild grey seal pups demonstrated that vocal production learning influenced the development of their pup calls. Independent groups of animals copied unknown frequency modulation sequences and individual calls played back to them depending on the kind of playback they were exposed to [50].…”
Section: Pinnipedsmentioning
confidence: 99%